2003
DOI: 10.1002/humu.10194
|View full text |Cite
|
Sign up to set email alerts
|

RettBASE: The IRSA MECP2 variation database—a new mutation database in evolution

Abstract: Communicated by Jaime CuticchiaRett syndrome (RTT) is a neurodevelopmental disorder affecting primarily females, with an incidence of around 1 in 15,000 females. In 1999, mutations in the X-linked gene methyl-CpG-binding protein 2 (MECP2) were first reported in RTT subjects, and since that time there have been a number of publications describing cohorts of patients and their mutations. In addition, MECP2 mutations have been reported in patients who do not fit the diagnostic criteria for Rett syndrome. We have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(132 citation statements)
references
References 29 publications
3
124
0
5
Order By: Relevance
“…The exact coincidence between the four residues crucial to the MeCP2-TBL1/TBLR1 interaction and the four residues mutated in RTT makes it highly likely that TBL1 and TBLR1 are essential partners of MeCP2. It is notable that over 200 independent cases of the R306C mutation have been reported, whereas mutation of P302 to R, L, or A has been seen 23 times (32). Missense mutations at K305 and K304 are rarer, having been reported only four and two times, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact coincidence between the four residues crucial to the MeCP2-TBL1/TBLR1 interaction and the four residues mutated in RTT makes it highly likely that TBL1 and TBLR1 are essential partners of MeCP2. It is notable that over 200 independent cases of the R306C mutation have been reported, whereas mutation of P302 to R, L, or A has been seen 23 times (32). Missense mutations at K305 and K304 are rarer, having been reported only four and two times, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, missense substitutions at each of these four residues (P302, K304, K305, and R306) are reported in multiple independent cases of RTT. On the other hand, pathological substitutions at other NID residues are not reported in a database with over 1,000 RTT mutations (32). The cocrystal structure explains in molecular detail why known RTT mutations in the NID likely prevent association with the NCoR/SMRT corepressor complex.…”
Section: Mecp2mentioning
confidence: 92%
“…27,28 Mutations in MECP2 were first reported in 1999, 29 and subsequent screening of RTT patients has shown that almost 90 -95% of classical RTT have pathogenic mutations. 30 To date over 200 individual nucleotide changes which cause pathogenic mutations have been described (Figure 4, RettBASE; mecp2.chw.edu.au 31 and MeCP2.org.uk); however, the eight most commonly occurring missense and nonsense mutations account for almost 70% of all mutations, and small deletions associated with a deletion hotspot in the C-terminal region of the MeCP2 protein account for an additional 9% of pathogenic mutations. Mutations are found throughout the gene, and more recently large deletions (kilobases in size) that delete whole exons have also been identified in a proportion of patients who were previously considered to be mutation negative, and are more commonly found in individuals with classical (36%; 46 out of 128) than atypical (3%; seven out of 229) RTT cases.…”
Section: Mutations In Mecp2mentioning
confidence: 99%
“…2 The first line of genetic testing involves mutation screening and sequencing of exons 3 and 4 for small sequence changes. 3 Over 200 MECP2 mutations have been identified 4 with some point mutations (p.R106W, p.R133C, p.R168X, p.R255X, p.R270X, p.R294X, p.R306C and p.T158M) occurring more commonly. Subsequent to sequencing, multiplex ligation-dependent probe amplification (MLPA) has also became available for the detection of deletions of one or more exons.…”
Section: Introductionmentioning
confidence: 99%